A new species of Apostolepis (Serpentes, Dipsadidae, Elapomorphini) from the Cerrado of Central Brazil - França, Daniella. P. F.; Barbo, Fausto E.; Silva-Júnior, Nelson J.; Silva, Helder L. R.; Zaher, Hussam (Zootaxa, 2018)
We describe a new species of the genus Apostolepis found near São Salvador Hydroelectric Power Plant, municipality of São Salvador do Tocantins, in the central Cerrado ecoregion. The new species is distinguished from its congeners by the following combination of characters: presence of eleven dorsolateral stripes, five infralabial scales and the lack of preoculars scales. The new species shares some external characteristics mainly with A. arenaria, A. gaboi and A. nelsonjorgei, with which it is compared.